The Dynamic and the Role of Migration in the Economic and Social Development of Albania - Sota, Jani (Richtmann Publishing, 2011)
This paper addresses the dynamic of Albanian migration during the last decade, focusing mainly on the dichotomy of push-pull factors, the migratory project and brain-drain trends. The one of the country, migration has only scarcely and economic development of research and academic debate in Albania. What has been said op to now on Albanian immigrants in Italy, mainly by press and media, had mostly been based on the accredited images and not on the fielde-research on the presence and contribution of immigrants to the country, labour market and society. This paper aims to: i) study the behavior of Albanian migrants, related to the creation, sending, amount and the usage of rimesses and to discover their new features; ii) provide information on the flow of rimesses of legal and illegal international migrants, and on the factors affecting them; iii) provide the respective findings for the studied issues, and give some recommendations on that bass.